The Human Milk-derived Peptide Drives Rapid Regulation of Macrophage Inflammation Responses in the Neonatal IntestineSummary - Fuqiang Yuan; Xu Han; Masha Huang; Yinglin Su; Yiting Zhang; Mengyuan Hu; Xiang Yu; Weilai Jin; Yun Li; Le Zhang (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: The interactions between human milk and the regulation of innate immune homeostasis in newborns, and their impact on intestinal health, are not fully understood. This study aimed to explore the role of peptides in human milk extracellular vesicles (EVs) in this process. Methods: A comprehensive screening of peptides within human milk EVs was performed, leading to the identification of a beta-casein-derived peptide (CASB135-150). The effects of CASB135-150 on intestinal injury were evaluated in a rat necrotizing enterocolitis (NEC) model. Immunofluorescence analysis was used to determine its distribution, and its impact on NF-κB signaling and inflammation was studied in bone marrow-derived macrophages (BMDMs) and intestinal macrophages. Protein-protein interaction (PPI) analysis, single-cell RNA-seq (scRNA-seq), and co-immunoprecipitation (co-IP) experiments were conducted to explore the mechanism underlying CASB135-150 function. Results: CASB135-150 significantly mitigated intestinal injury in the rat NEC model. Immunofluorescence analysis revealed that CASB135-150 could target intestinal macrophages and rapidly inhibited NF-κB signaling and reduced inflammation. ScRNA-seq analyses indicated a strong association between FHL2 and NEC development, and co-IP confirmed the interaction between CASB135-150 and FHL2. CASB135-150 disrupted the FHL2/TRAF6 complex, reducing TRAF6 protein levels. Mutation of key amino acids in CASB135-150 disrupted its interaction with FHL2 and abolished its ability to inhibit NF-κB signaling, which also prevented its protective effect in vivo. RNA-seq of intestinal tissue further highlighted the impact of CASB135-150 on the NF-κB signaling pathway. Conclusions: Our study identifies CASB135-150, a novel peptide in human milk EVs, that rapidly regulates macrophage inflammatory responses and protects against NEC-induced intestinal injury. These findings provide new insights into the role of human milk in modulating the infant immune system and intestinal health.